2023
DOI: 10.3390/plants12102047
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of One-Time Fertilization Scheme Achieved the Balance of Yield, Quality and Economic Benefits of Direct-Seeded Rice

Abstract: There is limited information available to assess the impact of one-time fertilization on the yield, quality, and economic benefits of direct-seeded rice. This study reports the effects of three one-time fertilizer treatments (BBU1, BBU2, and BBU3) on the yield, quality, and economic benefits of direct-seeded rice, where controlled-release nitrogen (N) fertilizer (CRNF) provided 50%, 60%, and 70% of the total N (270 kg N ha−1), and the control treatment (CK) was a split application of conventional urea (CU). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 57 publications
0
0
0
Order By: Relevance
“…The results of our own research have confirmed the influence of urea application, especially localized fertilization, on the total content of nitrogen in biomass and nitrate accumulation in plant tissue observed by other authors [37,40,41], and, in consequence, the percentage of NO 3 -N in the total N content.…”
Section: Content Of Total Nitrogen and Nitrate Nitrogen In Plantssupporting
confidence: 90%
“…The results of our own research have confirmed the influence of urea application, especially localized fertilization, on the total content of nitrogen in biomass and nitrate accumulation in plant tissue observed by other authors [37,40,41], and, in consequence, the percentage of NO 3 -N in the total N content.…”
Section: Content Of Total Nitrogen and Nitrate Nitrogen In Plantssupporting
confidence: 90%